Colistin-induced acquired Bartter-like syndrome: an unusual cause of meltdown. Issue 2 (5th February 2020) - Tabish, Mohammad; Mahendran, Manjit; Ray, Animesh; Vikram, Naval Kishore
Abstract : Colistin-induced nephrotoxicity is commonly associated with elevation of serum creatinine level or a reduction of urine output. Uncommonly, tubulopathy associated with colistin has been reported. Here we present a unique case of a 46-year-old man who developed polyuria, hypokalaemia, hypocalcaemia, hypomagnesemia and metabolic alkalosis after 3 days of therapy with intravenous colistimethate sodium. After ruling out other causes, a diagnosis of colistin-induced acquired Bartter syndrome was made. The patient required daily aggressive intravenous repletion of fluids and electrolytes. However, polyuria and metabolic abnormalities abated only after drug discontinuation.